Prasugrel vs. clopidogrel in acute coronary syndrome patients treated with prasugrel. (23rd September 2014) - Olson, W. H.; Ma, Y.‐W.; Laliberté, F.; Lefebvre, P.; Crivera, C.; Schein, J. R.; Fields, L. E.; Dea, K.; Germain, G.; Lynch, S. M.
Summary What is known and objective Current guidelines recommend a combination of clopidogrel and aspirin for management of patients who have experienced an acute coronary syndrome (ACS). Additional antiplatelet agents have been recently approved. Few comparative effectiveness studies are available for these new agents. Accordingly, we evaluated effect on time to hospital admission and resource utilization (number of hospitalizations, ER visits and outpatient visits) of prasugrel vs. clopidogrel in prasugrel‐treated patients as assessed in a matched cohort. Methods Based on the Truven Health Analytics MarketScan database from 01 January 2009 through 31 July 2012, a retrospective prasugrel–clopidogrel matched cohort was created. Inferences for average treatment effect over 1 and 12 months on time to hospitalization and resource utilization were performed by (i) frequentist Kaplan–Meier estimation with a Cox proportional hazard model and Lin's cost history method for censored resource utilization outcomes and (ii) Bayesian discrete‐time hazard and negative binomial models. Results and discussion The 10 963 matched pairs were well balanced on baseline characteristics. Frequentist analyses of time to hospital admission over 365 days and mean all‐cause resource utilization over 30 and 365 days showed no statistical differences between prasugrel and clopidogrel (P‐values > 0·05). Based on Bayesian analysis of time to admission over 12 months, there was positive evidence of equivalence (0·987 probability of equivalence at a 10% equivalence margin and a Bayes factor of 0·611). Although the frequentist analyses for number of all‐cause hospitalizations showed a lack of a significant difference at Months 1 and 12, the Bayesian data analysis showed positive evidence of superiority of clopidogrel at Month 1 (Bayes factor: 5·369); however, at Month 12, there was little evidence of superiority of one treatment over the other (Bayes factor: 0·422). What is new and conclusion Using frequentist and Bayesian data analyses, in prasugrel‐treated patients, clopidogrel was equivalent to prasugrel for time to hospital admission over 12 months and there was positive evidence that it was superior to prasugrel for number of hospitalizations over the first month of treatment.